Social Innovation and Institutional Capacity in Latin America - Arenilla Sáez, Manuel (Revista del CLAD Reforma y Democracia, 2017)
The current economic and financial crisis has caused that the more developed countries are giving up the old belief in an omnipotent State and an unlimited level of wellbeing, while in Latin America is questioning the extension and consolidation of basic public services. Today, the ability of States to deal with the diversity of citizen demands and needs, to bring public action to the whole population and to combat poverty is questioned. To this is added the loss of public confidence in public institutions and their members and leaders.We are experiencing profound changes in the society and the market that show that they are assuming a growing role in the satisfaction of the needs of the community. Thus appears an enlarged reality of the public service, which can no longer be referred to the administrative or state. Simultaneously, the State expands its role as an enabler, guarantor and activator of society and is required to be oriented towards inclusion, participation, representation and effective partnerships.In this context rises up the approach of social innovation that feeds on the evolution of ideas and governance of previous decades and the principles of the knowledge society, such as collaboration and the connection of talent, and which is being built primarily from international organizations and governments. One of its main objectives is the coproduction of public services in order to promote the renewal of the public sector and to cover its insufficiencies.It will be maintained that the characteristics of institutional development condition social innovation initiatives, specifically the characteristics that define institutional capacity, as it has been observed in most Latin American countries in the last decade with the guarantee and extension of public services. The shortcomings in the coverage of these and the rest of unsatisfied needs show a wide field of action of social innovation in Latin America.
Keywords: Administrative Innovation; Public Administration; Institutional Development; Administrative Capability: Public Services; Social Context; Latin America